KONSEP KOPERASI MOH. HATTA DAN RELEVANSINYA DENGAN PERKEMBANGAN KOPERASI SYARIAH - Anggianti Asti (UIN Siber Syekh Nurjati Cirebon, 2016)
ABSTRACT The conceptor of the cooperative concept in Indonesia is Mohammad Hatta, the Father of Cooperatives. The cooperative is formed by a group of people who have all the same to work together, for the welfare of members and the community. Cooperative is expected to be the economic support of the people to be able to set the economy so that there is no imbalance in the economic layer in Indonesia. However, in practice transactions, cooperatives use interest, whereas in Islam the use of interest is prohibited because it includes usury, that triggers the development of Sharia cooperatives.What is the concept of cooperative in Islamic economy, how cooperative concepts Mohammad Hatta and how the similarities and differences of both the concept and its relevance to the development of Sharia cooperatives?. Â In this study, the authors use a qualitative approach, namely to gain a deep understanding, then taking data through literature review, the books and then analyzed.There is a difference between the transaction in Mohammad Hatta cooperative concept, ie in transactions still use interest (riba) whereas in the Qur'an clearly prohibited its use. However, in Shariah cooperative transaction system using profit sharing as an alternative to interest (riba), Sharia cooperative forbids interest and carries moral ethics by looking at halal and haram rules in conducting business transactions.Keywords: cooperatives, Sharia cooperatives, cooperation.ABSTRAKPerumus konsep koperasi di Indonesia ialah Mohammad Hatta, Bapak Koperasi. Koperasi dibentuk oleh sekelompok orang yang telah sepakat untuk mengadakan kerja sama dan untuk mensejahterakan anggota dan umumnya masyarakat. Koperasi diharapkan menjadi penopang ekonomi rakyat untuk dapat mensejahtarakan ekonomi sehingga tidak ada ketimpangan dalam lapisan ekonomi di Indonesia. Namun pada praktek transaksi koperasi menggunakan bunga, padahal dalam agama Islam penggunaan bunga dilarang karena termasuk riba. Hal itu memicu adanya perkembangan koperasi Syariah.Bagaimanakonsep koperasi dalam ekonomi Islam, bagaimana konsep koperasi Mohammad Hatta, bagaimana persamaan dan perbedaan dari kedua konsep tersebut dan relevansinya dengan perkembangan koperasi syariah. Pada penelitian ini penulis menggunakan pendekatan kualitatif, untuk mendapatkan pemahaman yang mendalam, kemudian pengambilan datanya melalui kajian pustaka, referensi dari buku-buku kemudian dianalisis.Ada perbedaan mengenai transaksi dalam konsep koperasi Mohammad Hatta, yakni dalam transaksinya masih menggunakan bunga (riba) padahal dalam Al-Qurâ€™an jelas dilarang penggunaannya.Sistem transaksi koperasi syariah menggunakan bagi hasil sebagai alternatif dari bunga (riba), koperasi syariah mengharamkan bunga dan mengusung etika moral dengan melihat kaidah halal dan haram dalam melakukan transaksi usahanya.Kata kunci: koperasi, koperasi Syariah, kerja sama.